Exploring Associations Between Playgroup Attendance and Early Childhood Development at School Entry in Australia: A Cross-Sectional Population-Level Study. (April 2020) - Sincovich, Alanna; Gregory, Tess; Harman-Smith, Yasmin; Brinkman, Sally Anne
Despite widespread utilization, research exploring associations between playgroup and child development is scarce. We analyzed a national data set measuring the holistic development of children aged 4 to 6 years who commenced school in Australia in 2015 (n = 104, 767), the Australian Early Development Census, to explore developmental differences between children who did and did not attend playgroup before school. Children who attended playgroup had better development at school entry relative to those who had not attended playgroup, after adjustment for a range of confounding factors. These differences were observed across all five developmental domains and were universal to children from a range of backgrounds. Results support the need for future research to explore the causal effects of playgroup on children's development.